MULOK BMR TEACHER COMMUNICATION STRATEGY IN INSTILLING THE PRINCIPLES OF MALAY CULTURAL IDENTITY IN STUDENTS - Shasrini, Tessa; Sukri, Al; Idawati, Idawati (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
This research aims to explain the communication strategy of the Mulok BMR teacher in cultivating the principles of Malay cultural identity. This research uses a qualitative descriptive method, which uses analytical data from interviews and observations of objects. The Mulok subject aims to provide knowledge, skills and behavior to students so that they have solid insight into environmental conditions and community needs in accordance with the values/rules that apply in their region and support the continuity of regional development and national development. Riau Malay Culture (BMR) is included in learning because Malay Culture has become a strong identity in the traditions of society in Riau Province. Therefore, the Riau Provincial government includes Riau Malay Culture as part of education and includes it in the curriculum. The results of this research show that the communication strategies used by teachers during the learning process are: 1) applying Malay language during the learning process 2) Involving Students in Cultural Activities 3) Story Based Learning 4) using visual media. By implementing these communication strategies, teachers can become the main agents in strengthening Malay cultural identity in students. That way, students can take pride in their cultural heritage and apply it in everyday life. This communication strategy can also open the door to a deeper understanding and appreciation of Malay culture.